Evaluating the efficiency of oil waste treatment plant in AL- Qayyarah Refinery - Iraq - Shahab ahmad, Younis; Tariq Ismail, Bashar (Tikrit Journal of Pure Science, 2024)
The study included an evaluation of the efficiency of AL-Qayyarah refinery oil waste treatment plant. For this purpose, monthly samples were collected for a period of six months from October 2023 until March 2024, the first station (before treatment) represents the water coming out of the crude oil filter units. As for the second station (after treatment) it is located in the refinery waste treatment unit, the site represents the treated water. many physical and chemical tests were conducted on water, they ranged of temperature values ​​before the treatment ranged between (17-33) compared to its value after the treatment (15-31), and the electrical conductivity values ​​before the treatment ranged between (295-405)µS/cm, while after the treatment it was (349-471)µS/cm. As for total dissolved solids, their average before the treatment was(182.5)mg/L, while their average after the treatment was(194.6)mg/L as for salinity, its values ​​ranged between(0.7-0.75) mg/L before the treatment and between (0.6 -0.8) mg/L after the treatment ,pH value before the treatment was between)6.12- 7.91( compared to its value after the treatment as it ranged between (6.81-7.95), while the values ​​of the chemical requirement for oxygen before the treatment were (85108)mg/L, Their concentrations values ​​after the treatment amounted to(73_125) mg/L, and polycyclic aromatic hydrocarbons (PAHs) (73.46-155.17) mg/L before the treatment, and after the treatment it reached (35.53-52.53) mg/L, while oils and greases reached values ​​that ranged between (26.16-165.68) mg/L before the treatment compared to their results after the treatment which ranged between (94.15-23.18)mg/L. Finally, the total organic carbon had an average value before treatment (134.1) mg/L, while after treatment their average values ​​reached (120.8) mg/L